Sociology of religion in America : a history of a secular fascination with religion - Blasi, Anthony J. (Studies in the history of religions, 2014)
Sociology of Religion in America tells the story of the controversies involved in the development of a scientific specialty that often makes news in America. The evidence it presents runs contrary to the many myths about the field.